THE IMPORTANCE OF MISPRONUNCIATION DETECTION IN NONNATIVE LANGUAGE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
: This article is based on providing basic information on mispronunciation detection in non-native language. In linguistics, mispronunciation is the act of pronouncing a word incorrectly. The matter of what is or is not mispronunciation is a contentious one, and there is disagreement about the extent to which the term is even meaningful. Languages are pronounced in different ways by different people, depending on such factors as the area they grew up in, their level of education, and their social class. Even within groups of the same area and class, different people can have different ways of pronouncing certain words.